CFTR-associated ligand is a negative regulator of Mrp2 expression - Li, Man (Am J Physiol Cell Physiol, 2016)
The multidrug resistance-associated protein 2 (Mrp2) is an ATP-binding cassette transporter that transports a wide variety of organic anions across the apical membrane of epithelial cells. The expression of Mrp2 on the plasma membrane is regulated by protein-protein interactions. Cystic fibrosis transmembrane conductance regulator (CFTR)-associated ligand (CAL) interacts with transmembrane proteins via its PDZ domain and reduces their cell surface expression by increasing lysosomal degradation and intracellular retention. Our results showed that CAL is localized at the trans-Golgi network of rat hepatocytes. The expression of CAL is increased, and Mrp2 expression is decreased, in the liver of mice deficient in sodium/hydrogen exchanger regulatory factor-1. To determine whether CAL interacts with Mrp2 and is involved in the posttranscriptional regulation of Mrp2, we used glutathione S-transferase (GST) fusion proteins with or without the COOH-terminal PDZ binding motif of Mrp2 as the bait in GST pull-down assays. We demonstrated that Mrp2 binds to CAL via its COOH-terminal PDZ-binding motif in GST pull-down assays, an interaction verified by coimmunoprecipitation of these two proteins in cotransfected COS-7 cells. In COS-7 and LLC-PK1 cells transfected with Mrp2 alone, only a mature, high-molecular-mass band of Mrp2 was detected. However, when cells were cotransfected with Mrp2 and CAL, Mrp2 was expressed as both mature and immature forms. Biotinylation and streptavidin pull-down assays confirmed that CAL dramatically reduces the expression level of total and cell surface Mrp2 in Huh-7 cells. Our findings suggest that CAL interacts with Mrp2 and is a negative regulator of Mrp2 expression.